Kinetic resolution of tert-butyl (RS)-3-alkylcyclopentene-1-carboxylates for the synthesis of homochiral 3-alkyl-cispentacin and 3-alkyl-transpentacin derivatives. - Bunnage, M; Davies, S; Parkin, R; Roberts, P; Smith, A; Withey, J (2004)
High levels of stereocontrol are observed in the conjugate addition of lithium dibenzylamide to tert-butyl (RS)-3-alkylcyclopentene-1-carboxylates (alkyl = Et, Bn), with addition occurring exclusively anti- to the 3-alkyl substituent. Treatment of a range of tert-butyl (RS)-3-alkylcyclopentene-1-carboxylates (alkyl = Et, Bn, (i)Pr, (t)Bu) with lithium (RS)-N-benzyl-N-[small alpha]-methylbenzylamide indicates that good enantiorecognition is observed (E > 80) in their mutual kinetic resolution. In these reactions, conjugate addition of the lithium amide occurs exclusively anti- to the 3-alkyl substituent, with subsequent C(1)-protonation occurring preferably anti- to the 2-amino group in the 3-Et, 3-Bn and 3-(i)Pr cases, giving predominantly the corresponding 1,2-syn-2,3-anti-diastereoisomers. Conjugate addition to (RS)-3-tert-butyl cyclopentene-1-carboxylate results in exclusive 2,3-anti -addition and a reversal in C(1)-protonation selectivity, giving predominantly the 1,2-anti-2,3-anti-diastereoisomer. Furthermore, the kinetic resolution of the tert-butyl (RS)-3-alkylcyclopentene-1-carboxylates (alkyl = Et, Bn, (i)Pr, (t)Bu) with lithium (S)-N-benzyl-N-alpha-methylbenzylamide proceeds efficiently, giving, at between 47 and 51% conversion, the resolved 3-alkylcyclopentene-1-carboxylates in >85 to >98% ee and the beta-amino ester products of conjugate addition in high de, consistent with E > 80 in each case. Subsequent deprotection of the 1,2-syn-2,3-anti-3-alkyl-beta-amino esters (alkyl = Et, Bn, (i)Pr) by hydrogenolysis and ester hydrolysis gives the corresponding 1,2-syn-2,3-anti-3-alkylcispentacins in >98% de and 98 +/- 1% ee. Selective epimerisation of the 1,2-syn-2,3-anti-3-alkyl-beta-amino esters (alkyl = Et, Bn, (i)Pr, (t)Bu) by treatment with KO(t)Bu in (t)BuOH gives the corresponding 1,2-anti-2,3-anti-3-alkyl-beta-amino esters in quantitative yield and in >98% de, with subsequent deprotection by hydrogenolysis and ester hydrolysis giving the corresponding 1,2-anti-2,3-anti-3-alkylcispentacin hydrochlorides in >98% de.